Avaliação de fatores determinantes do consumo de frutas e hortaliças por acadêmicos da área da saúde de uma universidade pública em Belém, Pará. - FERREIRA, Vanessa de Matos (2023)
Fruits and vegetables are foods rich in nutrients, fiber and bioactive compounds, whose intake is inversely associated with the occurrence of chronic non-communicable diseases. Despite this, the range of recommended consumption of these foods in the Brazilian population is not very prevalent. The reasons for this low consumption are diverse. Studies on these aspects in a university population in the North region are few. Thus, this study aimed to verify the relationship of fruit and vegetable consumption with factors that are barriers or facilitate its ingestion, socioeconomic, demographic, lifestyle and nutritional status of students from undergraduate health courses at the Federal University of Pará, city of Belém, State of Pará, Brazil. This is a cross-sectional study with a non-probabilistic sample by saturation of 113 adult students of both genders, enrolled in one of the courses in the area of health at that university. Data were collected through an online questionnaire and the questions sought to obtain social, demographic, economic, intake and facilitating and hindering factors for the consumption of fruits and vegetables, lifestyle, weight and height, and academic data. Descriptive statistics of the variables and multiple logistic regression analysis with alpha at 5% were performed. Of the total sample of students (n=113) participating in the survey, 76.1% are female, 76.1% are aged between 20 and 29 years, and 64.6% reported family income of up to 3 minimum wages. Only 8.8% of the population assessed reached the recommendation for fruit and vegetable intake described as ideal in the literature. And only 37.2% and 35.4% of the evaluated consume vegetables and fruits regularly. Among the main findings, it can be seen that people with an income greater than or equal to 6 minimum wages are 4.53 times more likely to consume vegetables regularly (p=0.014) than those with an income lower than this; people with an income greater than or equal to 6 minimum wages are 3.675 times more likely to consume fruit regularly (p=0.026) than those with less than this income. In addition, it can be seen that people who pointed out the lack of habit as a hindering factor for the ingestion of vegetables had the chances of regular consumption of these foods decreased by 75% (OR=0.25; p=0.008), and the complicating factor perishability reduced the chances of regular fruit consumption by 64% (OR=0.376; p=0.023); on the other hand, the facilitating factor eating habits increased the odds by 3.4 times for regular fruit consumption (OR=3.41; p=0.004). Therefore, there is an urgent need for greater knowledge of the factors that are associated with low consumption of fruits and vegetables, so that collective health strategies can be taken, aiming to favor practices and attitudes that lead to greater intake of these foods by the university population.